Analisa Pengaruh Sambaran Petir Pada Jaringan Distribusi 13,8 kV di BOB PT. BSP - Pertamina Hulu Bandar Pedada Menggunakan Software ATP-EMTP - Rahmad Wahyudi Syaifulloh; Eddy Hamdani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The purpose of this paper is to analize the effect of indirect lightning strikes on the 13.8 kV distribution network at BOB PT. BSP - Pertamina Hulu Bandar Pedada by using ATP-EMTP. Maximum induced voltage of indirect lightning is computed by using Rusck theory, then indirect lightning strikes are simulated by using ATP-EMTP. In this paper, five conditions are simulated. The first condition is the distribution line without the indirect lightning strikes with 15 kV lightning arresters and the ground wire is installed, the second condition is the indirect lightning strikes without the 15 kV lightning arresters and ground wire, the third condition is indirect lightning strikes with the ground wire is installed and without the 15 kV lightning arrester, the fourth condition is the indirect lightning strikes with 15 kV lightning arresters are installed and without the ground wire, and the fifth condition is the indirect lightning strikes with the 15 kV lightning arresters and ground wire is installed. The simulation results show that the ground wire is able to reduce the effect of the induced voltage from the indirect lightning strikes, the 15 kV lightning arresters are able to reduce the effect of the induced voltage from the indirect lightning strikes, and the best results are obtained when the ground wire and the 15 kV lightning arresters are installed on the distribution line.Keyword : Indirect lightning strikes, Rusck theory, lightning arresters, ground wire, medium voltage distribution line.